A new flat mite genus, Acaricis (Prostigmata: Tenuipalpidae), from Australian sedges (Cyperaceae) - Beard, J. J.; Gerson, U. (Zootaxa, 2009)
We describe two new species of false spider mite in a new genus, Acaricis gen. nov., collected from native Australian sedges (Cyperaceae). The new genus shares morphological characters with the genera Tenuipalpus Donnadieu and Prolixus Beard, Fan & Walter. All three genera have dorsal opisthosomal seta h2 long and attenuate. Acaricis shares the presence of a rostral shield with Tenuipalpus; and shares with Prolixus an elongate body shape, absence of dorsal seta c1, genua I with two setae, nude genua IV, and setae g1 being inserted anterior to g2. Acaricis differs from both genera in having four palpal segments, as opposed to one to three.